Dinamika Umat Islam Indonesia pada Masa Kolonial Belanda (Tinjauan Historis) - Sitti Aisyah (Rihlah : Jurnal Sejarah dan Kebudayaan, 2015)
This paper explains about dynamics of Moslem’s life in Indonesia on the era of the Ducth Colonialism. In history, before European came to Indonesia, Islam had increased in Indonesia and had become majority religion since 13th century in Sumatera island. There, established an Islamic Kingdom, namely Samudra Pasai, and then transformed to Aceh Darussalam kingdom, furthermore, in the early of 15th century, Islam had dominated the region of Malaka (as a center of Southeast Asia trade).When Islam had come in Indonesia, spreading of Islam started by Islamic Scholars with huge motivation. Beside spreading Islam, they were trading also. The important role of scholar could be tracked on the Islamization map which is directly similar with economic development and the establishment of Islamic kindoms.In several region had become the center of trading. International Moslems whom became to important exponent and made communities on the beach area. Through this community, Islam had introducted to the society.However since The Ducthman came to Indonesia, trade situation had changed. The Dutch colonized Indonesia, even the spreading of Islam had stopped, because the scholars focus on struggle against the Ducth penetration.DINAMIKA UMAT ISLAM INDONESIA PADA MASA KOLONIAL BELANDA (Tinjauan Historis)